PARTICIPATORY PLANNING OF GREEN AREA FOR HATYAI CITY MUNICIPALITY, THAILAND - Fithriana, Noora (FIA UB, 2013)
Abstract: Participatory Planning Of Green Area For Hatyai City Municipality, Thailand. The aim of this academic research is to recommend participatory planning of green area to Hatyai City Municipality, by addressing (1) what is plan of Hatyai City Municipality in relation to green area? (2) how many green areas are available under Ministerial Regulation B.E. 2543? and (3) how is public opinion about the availability of green areas and participation for planning of green areas? Referring to the internal documents, the plans of Hatyai City Municipality in relation to green area are the concept of city in the garden and the development of Hatyai Park. The analysis of vector data capture informs that there are 2.35 km2 green areas available in Hatyai City; with the most green areas is para rubber. Public parks are also available in Hatyai City; where Sri Phu Wa Natch Resevoir Park is the central distribution. The survey finds that most of the citizens of Hatyai City think that the availability of green areas in Hatyai City is not enough. Those who think that the availability of green areas is not enough would ever participate in planning for green areas in Hatyai City. Participatory planning of green area, therefore, may be proper for Hatyai City Municipality. Keywords: green area, planning, participatory